Development of precision apple production technologies in Institute of Water and Environmental Management - Riczu, Péter; Tamás, János; Mesterházi, Péter Ákos; Nagy, Gábor (Acta Agraria Debreceniensis, 2012)
From the precision agriculture point of view, by the rapid development of the investigated technological elements – global positioning system (GPS), remote sensing (RS), global information system (GIS) – the number of services, which were not available in the past, because of their speed, complexity or price are increasing. The high accuracy high-tech instruments provide opportunity to elaborate several fruit production technologies, which aim is creating and operating water and energy safe quality fruit production systems. To evaluate these possibilities, experience was carried out in the Study and Regional Research Farm of the University of Debrecen near Pallag with the use of a GreenSeeker 505 Hand Held™ Optical Sensor Unit, and its interface the Trimble AgGPS FmX Integrated Display board computer, and a ScanStation C10 laser scanner by Leica. The results show the absolute applicability of these equipments in precision horticulture.